2018
DOI: 10.1038/s42003-018-0163-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered minipigs model the major clinical features of human neurofibromatosis type 1

Abstract: Neurofibromatosis Type 1 (NF1) is a genetic disease caused by mutations in Neurofibromin 1 (NF1). NF1 patients present with a variety of clinical manifestations and are predisposed to cancer development. Many NF1 animal models have been developed, yet none display the spectrum of disease seen in patients and the translational impact of these models has been limited. We describe a minipig model that exhibits clinical hallmarks of NF1, including café au lait macules, neurofibromas, and optic pathway glioma. Spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 76 publications
0
64
0
Order By: Relevance
“…We found statistically smaller long bones (femur, tibia, humerus, ulna, metacarpals) in the NF1 +/ex42del minipigs compared to their wildtype siblings. Previous NF1 minipig studies found no difference in stature using external measurement of length and height 23 . However, prior studies have recorded strong association between femur measurement and human stature in adults 50 and children 51 and have been used as a surrogate measure of growth differences between rats 52 and pigs 53 .…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…We found statistically smaller long bones (femur, tibia, humerus, ulna, metacarpals) in the NF1 +/ex42del minipigs compared to their wildtype siblings. Previous NF1 minipig studies found no difference in stature using external measurement of length and height 23 . However, prior studies have recorded strong association between femur measurement and human stature in adults 50 and children 51 and have been used as a surrogate measure of growth differences between rats 52 and pigs 53 .…”
Section: Discussionmentioning
confidence: 65%
“…Weight was not statistically significantly different between NF1 +/ex42del and wildtype minipigs at any of the three study time points (4, 8 and 12 months of age). Previous studies have indicated a reduced weight NF1 minipigs using a small selected cohort (N = 3) 23 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations